Вещно-правовые способы защиты права собственности в Российской Федерации - Ryskina, Kseniya (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the property rights protection system in the civil law system of the Russian Federation. The author present the law instruments that owner and possessor are entitled to.